Diagnóstico da gestão ambiental em indústrias metalúrgicas em municípios de médio porte - Moro, Patrícia Dal (2014)
The population increase in the last half of the XXI century, following up the technological advancement, induced the accelerated development of the industries, what caused the increase in the environmental pollution caused by the solid residues. Faced with this fact, lots of consumers are interested in products that aim the minimization of the environmental impacts. Therefore the legislation has been even more demanding, which obligates the companies to be even more responsible, in relation to the environment and its operational strategy. This way, the industries are searching the environmental quality with the implementation of environmental management systems. These systems aim the creation of an environmental policy, the establishment of goals and objectives that seek the improvement, monitoring and measurement of its effectiveness, the problems correction, the analysis and review of the program so that the adequacy is possible. Besides allowing the company to control systematically its environmental development and promote continuous improvement in its operations. This assignment presents the environmental diagnosis in manufacturing of steel structures and metal frames of small and medium-size industries of the county of Marau-RS. The data refer to the ways of fabrication, waste generation, environmental programs, and others. The data was collected by documental research, interviews, meetings, and direct observations. After knowing the situation of the 18 studied industries, one company was selected in which was tried to know its productive process, where the waste generation in each section was raised, as well as the environment aspects and impacts. Therewith, an environmental management system was proposed with base in the "NBR ISO 14001" seeking continuous improvement, bringing bigger efficiency and competitive edge, reducing the environment impacts and improving the environmental development. For the implantation of the system we sought the company management commitment, afterward the aspects and impacts of the company being studied were collected in each department. To achieve the objectives of the system improvements were done, like the implementation of hoods in the painting booth and the creation of a waste deposit. It has been found that the studied industries have deficiency in environmental issues, for this, the implementation of an environmental management system in the industries of manufacturing of steel structures and metal frame, would be of a big importance, so that, it would be possible to control the environmental impacts, adequate de process of fabrication, besides obtaining economical and environmental gains